"Initial Services”, la nuova fase del programma Galileo - Lisi, Marco (GEOmedia, 2017)
With the Declaration of Initial Services, officially launched by the European Commission in Brussels on Thursday 15 December 2016, Galileo started to offering services to public authorities, businesses and citizens, free services of primary importance as the support to emergency operations, more accurate navigation for citizens, better time synchronisation for critical infrastructures and secure services for public authorities. The Declaration of Galileo Initial Services means that the Galileo satellites and ground infrastructure are now operationally ready. These signals will be highly accurate but not available all the time. In the coming years, new satellites will be launched to enlarge the Galileo constellation, which will gradually improve Galileo availability worldwide. The constellation is expected to be completed by 2020 when Galileo will reach full operational capacity.